Isolasi dan Pengamatan Pertumbuhan Bakteri pada Kulit Kayu Manis (Cinnamomum Burmannii) Asal Kerinci - Maura Maharani; Ardi Mustakim (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Cinnamon bark (Cinnamomum burmannii) is known to contain antibacterial active compounds such as cinnamaldehyde and eugenol. However, as a natural material collected from open environments, it can become a habitat for various microorganisms, including bacteria. This study aimed to isolate and observe bacterial growth found on cinnamon bark originating from Kerinci. Samples were collected from a local market and processed using serial dilution, then cultured on Nutrient Agar (NA) and incubated for 24–48 hours at room temperature. The results revealed the growth of bacterial colonies with diverse morphological characteristics, such as round shape, smooth edges, and cream to cloudy white colors. Gram staining indicated the presence of both Gram-positive and Gram-negative bacteria. Preliminary biochemical tests showed both catalase-positive and catalase-negative isolates. These findings suggest that despite the antibacterial properties of cinnamon bark, certain microorganisms are capable of surviving. The detected bacteria are likely to be either endophytic or environmental contaminants that have adapted. These results provide an initial insight into the local microbial diversity and open opportunities for further exploration of bacteria with biotechnological potential, while also supporting post-harvest quality control of spice products.